LOW PLASMA CORTISOL LEVEL IS A RISK FACTOR FOR ADULT ATOPIC DERMATITIS AND NEGATIVELY CORRELATED TO PLASMA LEVELS OF NOREPINEPHRINE AND INTERLEUKIN-4 - Wardhana, Made; Suata, Ketut; Suastika, Ketut (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2012)
Atopic dermatitis is a skin inflammatory disease characterized by hyperactivity of the humoral immune system with a typical onset in infancy or early childhood. Many studies have focused on the patho-physiological role of the immune system in atopic dermatitis, but since the stress hormone receptor was recognized on the surface of immune cells, it appeared that cortisol was prominent stress hormones in regulating the immune system. Some studies have shown that individuals with atopic diseases such as atopic dermatitis, allergic rhinitis and bronchial asthma had lower concentration of saliva cortisol than those with non-atopic conditions. With this evidence, it can be assumed that lower concentration of cortisol as the result of hypo-response of hypothalamus-pituitary-adrenal to stressor can increase and interleukin (IL-4) concentrations. Both substances stimulate lymphocyte T helper 2 (Th2) cells to synthesize IL-4, which has an important role in atopic dermatitis pathogenesis to increase hypersensitivity to various environmental allergens. Until recently, few studies are available concerning the low concentration of plasma cortisol as a risk factor for atopic dermatitis, as well as its correlation with plasma levels of and IL-4. The purpose of this study was to show that low concentration of plasma cortisol is a risk factor for atopic dermatitis and it is negatively correlated with and plasma IL-4. Matched pair case control design, involving 36 cases and 36 controls, was used to show that low concentration of cortisol is a risk factor for atopic dermatitis, and cross sectional design was applied to find out the negative correlation between cortisol and IL-4 in 88 samples consisting of 52 patients with atopic dermatitis and 36 healthy person or persons without atopy. The result of the case-control study showed that plasma cortisol concentration of the case group was significantly lower (4.89 + 2.1 ug/dl; CI 95 %; p < 0.001) than in those of the control group (9.12 + 2.33 ug/dl) at confidence level of 95%; p < 0.001. Multiple logistic regression analysis showed odd ratio of cortisol 3.45, which was higher than the ratio of other parameters such as IL-4, history of atopy and skin moisture. Plasma and IL-4 concentrations of the patients with atopic dermatitis were significantly higher than in the subjects without atopy. The correlation test indicated that plasma cortisol was negatively correlated to norepinephrine (r = - 0.68; p < 0.05), and IL-4 (r = - 0.55; p = 0.05) levels in patients with atopic dermatitis. Based on the above findings, it can be deduced that low concentration of plasma cortisol, being correlated to increased plasma levels of norepinephrne and interleukin-4, is a risk factor for atopic dermatitis in adult
Keywords: Atopic dermatitis, cortisol, , IL-4